CHIP-dependent termination of MEKK2 regulates temporal ERK activation required for proper hyperosmotic response - Maruyama, Takeshi (Nature Publishing Group, 2010)
The extracellular signal-regulated kinase (ERK) pathway is an important signalling pathway that regulates a large number of cellular processes, including proliferation, differentiation and gene expression. Hyperosmotic stress activates the ERK pathway, whereas little is known about the regulatory mechanisms and physiological functions of ERK activation in hyperosmotic response. Here, we show that MAPK/ERK kinase kinase 2 (MEKK2), a member of the MAPKKK family, mediated the specific and transient activation of ERK, which was required for the induction of aquaporin 1 (AQP1) and AQP5 gene expression in response to hyperosmotic stress. Moreover, we identified the E3 ubiquitin ligase carboxyl terminus of Hsc70-interacting protein (CHIP) as a binding partner of MEKK2. Depletion of CHIP by small-interference RNA or gene targeting attenuated the degradation of MEKK2 and prolonged the ERK activity. Interestingly, hyperosmolality-induced gene expression of AQP1 and AQP5 was suppressed by CHIP depletion and was reversed by inhibition of the prolonged phase of ERK activity. These findings show that transient activation of the ERK pathway, which depends not only on MEKK2 activation, but also on CHIP-dependent MEKK2 degradation, is crucial for proper gene expression in hyperosmotic stress response.